2011
DOI: 10.1097/cad.0b013e3283425c14
|View full text |Cite
|
Sign up to set email alerts
|

Irinotecan and radiosensitization in rectal cancer

Abstract: Neoadjuvant radiation therapy with concurrent 5-fluorouracil-based chemotherapy is currently considered the standard of care for locally advanced rectal cancer. Pathologically complete response is a desirable outcome and has been associated with increased disease-free survival. There is a need to improve on this approach given that only approximately 10% achieve a pathologically complete response. Irinotecan has an established role in the treatment of metastatic rectal cancer. Both in-vitro and in-vivo data ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 40 publications
2
20
0
Order By: Relevance
“…Furthermore, irinotecan is metabolized to SN-38, a more active metabolite. In vitro studies found synergy was dependent on drug concentration and timing, with increased radiosensitivity present only when the drug was present at the time of, or shortly after (24-48 h.) radiation [51,52].…”
Section: Irinotecanmentioning
confidence: 99%
“…Furthermore, irinotecan is metabolized to SN-38, a more active metabolite. In vitro studies found synergy was dependent on drug concentration and timing, with increased radiosensitivity present only when the drug was present at the time of, or shortly after (24-48 h.) radiation [51,52].…”
Section: Irinotecanmentioning
confidence: 99%
“…Despite the promise of the above studies, no phase III trial of concurrent irinotecan has yet been reported. This will be rectified in the future by the ongoing UK ARISTOTLE trial, which will complete accrual (target 600 patients) in mid‐2018.…”
Section: Additional Chemotherapy Agents To Enhance Radiosensitivitymentioning
confidence: 99%
“…Despite the promise of the above studies, no phase III trial of concurrent irinotecan has yet been reported 58 .…”
Section: Irinotecanmentioning
confidence: 99%
“…8 Several chemotherapeutic agents that have improved survival in the adjuvant or metastatic setting for the management of colon cancer have been evaluated as possible radiosensitizers in rectal cancer. 9 These agents include irinotecan, 10 oxaliplatin, 11 bevacizumab, 12 and cetuximab. 12 However, none of these compounds has demonstrated superiority to 5-FU in terms of achieving a substantially increased rate of pCR.…”
mentioning
confidence: 99%